The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1111/sms.12668
|View full text |Cite
|
Sign up to set email alerts
|

Different visual stimuli affect body reorientation strategies during sidestepping

Abstract: Sidestepping in response to unplanned stimuli is a high-risk maneuver for anterior cruciate ligament (ACL) injuries. Yet, differences in body reorientation strategies between high- and low-level soccer players prior to sidestepping in response to quasi-game-realistic vs non-game-realistic stimuli, remain unknown. Fifteen high-level (semi-professional) and 15 low-level (amateur) soccer players responded to a quasi-game-realistic one-defender scenario (1DS) and two-defender scenario (2DS), and non-game-realistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 29 publications
2
27
1
1
Order By: Relevance
“…68) states that directional changes must be planned and initiated in the step before the turn to facilitate effective COD performance. This is substantiated by previous studies that have reported athletes make anticipatory postural adjustments (APA) in the step prior to (penultimate foot contact (PFC)) the COD (final foot contact (FFC)), demonstrating kinematic changes in foot placement, trunk lean and rotation, and head rotation (37,51,60,69,93,95). Furthermore, braking characteristics such as greater braking forces and external knee flexor moments (KFM) have been reported in the step prior (PFC) to CODs ≥ 60˚ (20,25,(42)(43)(44)(45), highlighting the importance of the PFC during extreme directional changes.…”
Section: P a G E |supporting
confidence: 68%
“…68) states that directional changes must be planned and initiated in the step before the turn to facilitate effective COD performance. This is substantiated by previous studies that have reported athletes make anticipatory postural adjustments (APA) in the step prior to (penultimate foot contact (PFC)) the COD (final foot contact (FFC)), demonstrating kinematic changes in foot placement, trunk lean and rotation, and head rotation (37,51,60,69,93,95). Furthermore, braking characteristics such as greater braking forces and external knee flexor moments (KFM) have been reported in the step prior (PFC) to CODs ≥ 60˚ (20,25,(42)(43)(44)(45), highlighting the importance of the PFC during extreme directional changes.…”
Section: P a G E |supporting
confidence: 68%
“…1 ). Unfortunately, however, the results of Jones et al [ 62 ] indicate that unanticipated situations do not allow postural adjustments prior to the FFC to evoke greater braking force characteristics during the PFC; however, it should be noted that the unanticipated COD task involved responding to a light stimuli, which is more challenging than using a sports-specific stimulus [ 63 , 64 ], and it also lacks specificity to the sporting situations where athletes typically scan and process kinematic and postural cues prior to changing direction [ 65 ]. Further research is warranted investigating the role of the PFC during unanticipated tasks utilising sports-specific stimuli.…”
Section: Effect Of Angle On Cod Biomechanicsmentioning
confidence: 99%
“…Changing direction is described as a multi-step action [ 61 ], with research indicating the step(s) prior to the COD are pivotal in deceleration and initiating effective CODs [ 34 38 , 53 , 58 – 60 , 64 , 66 , 128 133 ]. Specifically, researchers have shown that the greater braking force characteristics demonstrated in the PFC during COD can alleviate knee joint loading [ 36 38 ] and also facilitate faster turning performance [ 58 – 60 ]; however, only two studies have examined the effect of approach velocity on PFC biomechanics.…”
Section: Effect Of Velocity On Cod Biomechanicsmentioning
confidence: 99%
“…Planned CoDs that have been used previously in the assessment of CoD following ACLr (i.e., carioca, shuttle, co contraction, T test, cutting) without temporal constraints may afford sufficient time for the adoption of a 'safer' and more optimal movement execution. For example, the support foot placement strategy (i.e., more medial to the pelvic midline) prior to initial contact of the push-off foot to initiate the direction change, thus lowering the mechanical stress on the knee [47]. Performing an unplanned task can be in response to either generic (react against 2 dimension planned and unplanned light-based directional arrows) and quasi-realistic (react against 1 or 2 defenders' scenarios in a 3-dimension video projection) external stimuli.…”
Section: Planned Vs Unplannedmentioning
confidence: 99%